The Effect of Practical Life Activity towards the Improvement of An Autistic Child’s Fine Motor Skill - Indri Winegal; Sudarsini Sudarsini; Eka Pramono Adi (Department of Special Education, 2018)
There is an attempt to help autistic child’s in improving their fine motor skill, one of them is through practical life activities. This research was aimed at improving the fine motor skill of an autistic child’s through practical life activities. This research implemented Single Subject Research Method with A-B-A design. The data were analyzed using the technique of visual analysis in the form of data graphic both in between the condition and in the condition. The findings presented the percentage of 0% overlap. Besides, the data analysis showed that the children’s fine motor skill improved in Baseline-2 (A2) or control condition with stable score of 75%, which was higher that Baseline-1 (A1) or condition before intervention was given, with the stable score of 53,12%. In conclusion, Practical Life activity could improve the fine motor skill of the autistic.